The Filipino Americans - Stern, Jennifer (New York Chelsea House, 1989)
Discusses the history, culture, and religion of the Filipinos, factors encouraging their emigration, and their acceptance as an ethnic group in North America.
Includes index.
Keywords: Filipino Americans -- Juvenile literature; Filipino Americans